Instructors’ Opinion on Management Factors Affecting Quality Assurance Effectiveness of Southern College of Technology - Pechrit, Saowapak (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The purpose of this research was to study Instructors’ Opinion on Factors Affecting Quality Assurance Effectiveness of Southern College of Technology. The population used in this study consisted of 51 instructors. A questionnaire developed by the researcher was used in collecting data from the population. The reliability coefficients of the overall questionnaire was 0.86. Percentage, mean and standard deviation were performed. The findings revealed that the overall management factor affected the effectiveness of the quality assurance at moderate level. The general management affected the effectiveness of the quality assurance at high level, the management of human resources, the materials and equipment, and the budget at moderate level. The findings indicated that general management and personnel had a high influence on the effectiveness of the operation of quality assurance so the college should concentrate on the two factors in order to increase effectiveness.